(untitled) (Indian Journal of Arid Horticulture, 2025)
Major cauliflower growing area of Udaipur district was surveyed to know the severity of pathogens on development of black rot. An environmental factor essentially affects the intensity and spread of cauliflower black rot. Cauliflower plants inoculated at one week intervals, throughout the investigation during the rabi season (October 2003 to February-2004). The severe disease development was recorded during the month of January when the humidity between 82-89 per cent and temperature ranges between 23-30° prevailed. While the disease development was trace during October and November and low in the month of December. Disease progressed faster during the crop growth period in January and February under cage house condition. Regression and correlation coefficient important environment factors in relation to the progress of disease were noticed. The disease curve had three distinct phase (period) viz, initial inoculum build up or disease establishments, rapid disease progress and disease establishment. Regression showed positive picture and negative correlation was obtained for maximum and minimum temperature, which signified their role of the rapid disease progress period. However, maximum infection was noticed, when RH range between 82-89 per cent. It was observed that disease development gained momentum when the maximum temperature started lowering down from 33° C, minimum temperature below 23°C adversely affect the disease development in cauliflower.